Antidotes to anthrax lethal factor intoxication. Part 1: Discovery of potent lethal factor inhibitors with in vivo efficacy - Jiao, Guan-Sheng (2010)
Sub-nanomolar small molecule inhibitors of anthrax lethal factor have been identified using SAR and Merck L915 (4) as a model compound. One of these compounds (16) provided 100% protection in a rat lethal toxin model of anthrax disease.